Stress-Dependent Association Between Polygenic Risk for Schizophrenia and Schizotypal Traits in Young Army Recruits. (13th June 2017) - Hatzimanolis, Alex; Avramopoulos, Dimitrios; Arking, Dan E; Moes, Anna; Bhatnagar, Pallav; Lencz, Todd; Malhotra, Anil K; Giakoumaki, Stella G; Roussos, Panos; Smyrnis, Nikolaos; Bitsios, Panos; Stefanis, Nicholas C
Abstract: Schizotypal personality traits may increase proneness to psychosis and likely index familial vulnerability to schizophrenia (SZ), implying shared genetic determinants with SZ. Here, we sought to investigate the contribution of common genetic risk variation for SZ on self-reported schizotypy in 2 ethnically homogeneous cohorts of healthy young males during compulsory military service, enrolled in the Athens Study of Proneness and Incidence of Schizophrenia (ASPIS, N = 875) and the Learning on Genetics of Schizophrenia Spectrum study (LOGOS, N = 690). A follow-up psychometric assessment was performed in a sub-sample of the ASPIS ( N = 121), 18 months later at military service completion. Polygenic risk scores (PRS) for SZ were derived based on genome-wide association meta-analysis results from the Psychiatric Genomics Consortium. In the ASPIS, higher PRSSZ significantly associated with lower levels of positive (ie, perceptual distortions), disorganization and paranoid facets of schizotypy, whereas no association with negative (ie, interpersonal) facets was noted. Importantly, longitudinal data analysis in the ASPIS subsample revealed that PRSSZ was inversely associated with positive schizotypy at military induction (stressed condition) but not at follow-up (nonstressed condition), providing evidence for environmental rather than SZ-implicated genetic influences. Moreover, consistent with prior reports, PRSSZ was positively correlated with trait anxiety in the LOGOS and additionally the recruits with higher PRSSZ and trait anxiety exhibited attenuated paranoid ideation. Together, these findings do not support an etiological link between increased polygenic liability for SZ and schizotypy, suggesting that psychosocial stress or trait anxiety may impact schizotypal phenotypic expressions among healthy young adults not genetically predisposed to SZ.